Reliability Generalization of the Medical Student Stressor Questionnaire - Montano, Mason A.; Montano, Samuel A.; Harrison, Jennifer L.; Kivisalu, Trisha M. (International Journal of Medical Students, 2022)
Background: Medical education is known to be stressful. Thus, medical schools have begun amending curricula to incorporate holistic wellness and stress reduction. Assessing medical student stressors is key to curricula development as well as the selection of appropriate reliable measures. This study investigated reliability reporting for studies using the Medical Student Stressor Questionnaire (MSSQ), as no study of this kind currently exists via employing Reliability Generalization (RG). Methods: A meta-analytic method, RG, was used to analyze the reliability reporting practices and reliability coefficients, in the form of Cronbach’s alpha coefficient, for the MSSQ. While a total of 18 studies were initially isolated related to the MSSQ, only those studies reporting reliability based on their sample (n = 8) were included in the final analysis. Blind coding was utilized and percent agreement among raters was excellent (95.18%). Results: Reliability estimates reported for the total scale fell within the excellent range (Range alpha coefficient (?) = 0.800 – 0.970; Mean alpha coefficient (M?) = 0.933, Standard Deviation alpha coefficient (SD?) = 0.050). A larger percent of males was negatively correlated to academic stressors while the number of females in studies was negatively correlated with social, drive, group activities and inter/intrapersonal aspects of medical student stressors. Conclusions: Outcomes provide useful suggestions, implications, and future recommendations regarding the use and application of the MSSQ. Medical student stress is essential to assess via measures which demonstrate robust reliability. Insights into sources of stress can offer important feedback to making specific changes to medical school curricula.